2003
DOI: 10.1038/sj.ijo.0802484
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in the relationship between fasting leptin and BMI in children

Abstract: OBJECTIVE:To compare the relationship between fasting serum leptin levels and body mass index (BMI) in children from different ethnic groups. SUBJECTS: Children aged 6-10 y from rural Gambia (n ¼ 471) and central Italy (n ¼ 839). MEASUREMENTS: Anthropometry (z-score of BMI) and fasting serum leptin concentrations. RESULTS: The Italian children had significantly higher mean BMI z-scores than the Gambian children (males: Italy 1.58, Gambia À1.44, Pr0.0001; females: Italy 1.33, Gambia -1.42, Pr0.0001) and signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…It illustrates a comparison of leptin levels in undernourished Gambian children compared with an age-and sex-matched reference group from Italy. 41 Leptin levels show quite a shallow slope against body mass index (BMI, kg/m 2 ) for all individuals below the reference norm (i.e., zero standard deviation score). Most of the Italian children were above the reference norm indicating a chronic energy surplus that must be stored as fat.…”
Section: Leptin As a Starvation Hormone: Functionality At Low Levelsmentioning
confidence: 93%
“…It illustrates a comparison of leptin levels in undernourished Gambian children compared with an age-and sex-matched reference group from Italy. 41 Leptin levels show quite a shallow slope against body mass index (BMI, kg/m 2 ) for all individuals below the reference norm (i.e., zero standard deviation score). Most of the Italian children were above the reference norm indicating a chronic energy surplus that must be stored as fat.…”
Section: Leptin As a Starvation Hormone: Functionality At Low Levelsmentioning
confidence: 93%
“…A study of 74 African-American and Caucasian pre-pubertal children found no ethnic differences in leptin levels when adjusting for differences in body composition measured by DEXA (27). In contrast, a study comparing Italian and west African children aged 6–10 years found that at all levels of BMI, the Italian children showed a greater level of leptin than the Gambian children (28). However, the use of BMI in growing children and in inter-ethnic studies has its limitations.…”
Section: Discussionmentioning
confidence: 84%
“…Leptin levels were strongly correlated with indices of obesity (BMI and WC) in the whole group as well as in obese youths. However, a previous study [36] reported no correlation between leptin levels and BMI in obese youths, suggesting ethnic differences [37] .…”
Section: Discussionmentioning
confidence: 99%
“…In obese subjects, only the levels of leptin and IR were higher in girls compared to boys, otherwise, gender had no effect on all other parameters. Higher levels of leptin [34,35] , TG [36] and IR [37] and lower levels of ALT [38] have previously been reported in females compared to males. The stage of puberty had a marked influence on certain components of MetS, as both the non-obese and obese individuals in the higher puberty stage had significantly higher values for BMI, systolic BP, insulin, leptin, and IR compared to those at lower puberty stage, however, puberty status had no effect on diastolic BP, glucose, lipids, TG, UA and ALT.…”
Section: Discussionmentioning
confidence: 99%